Social representations of working children in university students of education - Suarez Ch., Jeny (2013)
The purpose of this study was to analize how a group of Education Faculty Students have their own social representations on working children, particulary how they conceive a working child, why a child works and about his or her family, but also how as future educators they will have a good management as social workers and they will succeed to establish a positive relationship with working children. The survey- a semistructured questionnairewas applied to 28 female students of the faculty of education and the results showed us the prevalence of the protectionist paradigm in relation to working children, but also a lack of a co-protagonism approach at all.